Foreign Direct Investment Volatility And Economic Growth In Asean-Five Countries - Choong, Chee-Keong; Liew, Venus Khim-Sen; Chan, Sok-Gee; Ch’ng, Huck-Khoon (HRMARS, 2011)
This study examines the role of foreign direct investment (FDI) volatility as a source of variability in five major ASEAN economies. Using bounds testing approach, we show that while FDI has positive and significant effect in all the ASEAN economies considered, its volatility retards long-run economic growth in Indonesia, Malaysia, the Philippines and Thailand. Moreover, FDI volatility can be welfare reducing even after controlling for other country-specific growth correlates. This finding is robust to different measures of FDI volatility.